Antiviral and immunomodulatory activity of curcumin: A case for prophylactic therapy for COVID-19. Issue 2 (February 2021) - Thimmulappa, Rajesh K.; Mudnakudu-Nagaraju, Kiran Kumar; Shivamallu, Chandan; Subramaniam, K.J.Thirumalai; Radhakrishnan, Arun; Bhojraj, Suresh; Kuppusamy, Gowthamarajan
Abstract: Coronavirus disease-19 (COVID-19), a devastating respiratory illness caused by SARS-associated coronavirus-2 (SARS-CoV-2), has already affected over 64 million people and caused 1.48 million deaths, just 12 months from the first diagnosis. COVID-19 patients develop serious complications, including severe pneumonia, acute respiratory distress syndrome (ARDS), and or multiorgan failure due to exaggerated host immune response following infection. Currently, drugs that were effective against SARS-CoV are being repurposed for SARS-CoV-2. During this public health emergency, food nutraceuticals could be promising prophylactic therapeutics for COVID-19. Curcumin, a bioactive compound in turmeric, exerts diverse pharmacological activities and is widely used in foods and traditional medicines. This review presents several lines of evidence, which suggest curcumin as a promising prophylactic, therapeutic candidate for COVID-19. First, curcumin exerts antiviral activity against many types of enveloped viruses, including SARS-CoV-2, by multiple mechanisms: direct interaction with viral membrane proteins; disruption of the viral envelope; inhibition of viral proteases; induce host antiviral responses. Second, curcumin protects from lethal pneumonia and ARDS via targeting NF-κB, inflammasome, IL-6 trans signal, and HMGB1 pathways. Third, curcumin is safe and well-tolerated in both healthy and diseased human subjects. In conclusion, accumulated evidence indicates that curcumin may be a potential prophylactic therapeutic for COVID-19 in the clinic and public health settings. Abstract : COVID-19, SARS-CoV-2, curcumin, antiviral, immunomodulator, therapeutics